2022
DOI: 10.1108/apjba-12-2020-0437
|View full text |Cite
|
Sign up to set email alerts
|

Creativity mindset as the organizational capability: the role of creativity-relevant processes, domain-relevant skills and intrinsic task motivation

Abstract: PurposeThe objective of this study is to examine the structural relationship between creativity-relevant processes, domain-relevant skills, intrinsic task motivation, creativity and the moderating effect of social environment (sufficient resources, workgroup support, realistic work pressure and lack of organizational impediments).Design/methodology/approachA total of 289 valid questionnaires were collected from engineering students in Malaysian universities to test the measurement as well as the structural mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Furthermore, the positive impact of domain-relevant skills on employee creativity has also been supported by empirical studies (e.g., Liu et al, 2017 ; Emami et al, 2023 ). Although Liu et al (2017) did not make direct assumptions regarding domain-relevant skills and employee creativity, the research results showed that domain-relevant skills can mediate the influence of high-performance human resource systems on employee creativity.…”
Section: Theory and Hypothesesmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the positive impact of domain-relevant skills on employee creativity has also been supported by empirical studies (e.g., Liu et al, 2017 ; Emami et al, 2023 ). Although Liu et al (2017) did not make direct assumptions regarding domain-relevant skills and employee creativity, the research results showed that domain-relevant skills can mediate the influence of high-performance human resource systems on employee creativity.…”
Section: Theory and Hypothesesmentioning
confidence: 75%
“…Their study is the first empirical study of domain-relevant skills, which lays a foundation for exploring the impact of domain-relevant skills on employee creativity. Additionally, Emami et al (2023) found that, when controlling for intrinsic motivation and creativity-relevant processes, domain-relevant skills are positively associated with the creativity of upcoming engineers. Based on the above review, it appears that domain-relevant skills can improve employee creativity.…”
Section: Theory and Hypothesesmentioning
confidence: 95%
“…In recent years, research on implicit theories of creativity, conceptualized in terms of laypeople’s inner beliefs regarding creativity, have been emerging and flourishing ( Karwowski, 2023 ). Notably, an increasing research attention has been paid to a subset of implicit theories of creativity (i.e., creative mindset ), which specifically pertains to people’s beliefs regarding the stable-versus-malleable nature of creativity ( Emami et al, 2023 ; Hua and Yang, 2024 ). Joining this line of research, the present study aimed to understand the effect of two types of creative mindset (i.e., growth and fixed creative mindsets ) on creative thinking and the associated underlying mechanism that may account for this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Real leadership involves encouraging and inspiring a group of people to work together toward a common objective (Ashfaq and Hamid, 2021;Bharadwaj et al, 2021;Emami et al, 2022;Torlak and Kuzey, 2019;Valaei et al, 2022). According to social exchange theory, the practice of organizational citizenship has been associated with improvement in areas such as justice, fairness, association excellence, and many more dynamic dimensions, including enhanced efficiency, lower intention to leave, and higher customer satisfaction (Podsakoff et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Real leadership involves encouraging and inspiring a group of people to work together toward a common objective (Ashfaq and Hamid, 2021; Bharadwaj et al. , 2021; Emami et al. , 2022; Torlak and Kuzey, 2019; Valaei et al.…”
Section: Introductionmentioning
confidence: 99%